THU0539 Sarcoidosis in spain: clinical and epidemiological characteristics at diagnosis in 1082 patients. (15th June 2017) - Pérez-Alvarez, R; Kostov, B; González, A García; Torre, R Gόmez De La; Dupla, M Lopez; Escalante, B De; Alguacil, A; Chara, J; Velilla, J; Rascόn, J; Morillo, JS Garcia; Feijoo, C; et al.
Abstract : Objectives: To characterize the main features at presentation of sarcoidosis in a large multicenter cohort from Southern Europe. Methods: In January 2016, the Autoimmune Diseases Study Group (GEAS-SEMI) created a national registry (SARCOGEAS) of patients with sarcoidosis. Sarcoidosis was diagnosed in agreement with the criteria proposed by the ATS/ERS/WASOG 1999 statement, and extrathoracic disease was classified with the 2014 WASOG instrument. Results: The cohort consisted of 1082 patients (82% biopsy-proven), including 618 (57%) women and 464 (43%) men, with a mean age at diagnosis of 47yrs; 140 (13%) patients were born outside Spain, 965 (89%) were White, 69 (6%) Hispanic, 30 (3%) Black/African American and 18 (2%) Asian. Thoracic involvement was present at diagnosis in 979 (90%) patients, including 437 (40%) patients with stage I, 374 (35%) with stage II, 123 (11%) with stage III and 26 (2%) with stage IV. The most frequently reported extrathoracic involvements at diagnosis were cutaneous in 385 (36%) patients, extrathoracic lymph nodes in 218 (20%), liver involvement in 151 (14%) and ocular involvement in 118 (11%). Potentially life-threatening WASOG involvements were reported in frequencies less than 10%, including neurological involvement in 77 (7%) patients, kidney involvement in 59 (5%) or cardiac involvement in 21 (2%). Therapeutic approaches at diagnosis included the use of oral glucocorticosteroids in 637 (59%) patients, immunosuppressive agents in 84 (8%, mainly methotrexate in 63 patients) and biological agents in 15 (1%, mainly infliximab in 10 cases). Conclusions: In this large series of sarcoidosis from Southern Europe, clinical presentation is dominated by adenopathies (both thoracic and extrathoracic) and cutaneous involvement (erythema nodosum), with lower frequencies in the main extrathoracic involvements than that reported in US and Japanese series. Disclosure of Interest: None declared